Pinene Rich Essential Oil from Eucalyptus tereticornis Leaves from Tarai and Bharar Areas of Uttar Pradesh - Shiva, M. P.; Paliwal, G. S.; Chandra, Kuldeep; Mathur, Manju (Indian Forester, 1984)
The results of analysis of the essential oil samples from Eucalyptus tereticornis leaves collected from six forest divisions of tarai and bhabar areas in U.P. as determined by Gas-liquid chromatography have been presented in this paper. The data on component percenlages given in this paper reveal that E. tereticornis oil is generally rich in pipenes which may prove to be a good source of pinenes for induslrial utilization in the manufacture of aromatic chemicals etc.